2016
DOI: 10.3892/etm.2016.3518
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin attenuates acute doxorubicin cardiotoxicity in rats via the suppression of oxidative stress, inflammation and apoptosis and the activation of FOXO3a

Abstract: Abstract. Doxorubicin (DOX) is one of the most effective chemotherapeutic drugs. However, its clinical use has been hampered due to the development of cardiotoxicity. Vitexin, which is the active ingredient of hawthorn leaf extract, has various biological activities, including antioxidant and anti-inflammatory actions. The present study aimed to investigate whether vitexin was able to protect against DOX-induced acute cardiotoxicity in model rats and the mechanisms of this protective effect were assessed. Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Treatment with Vitexin significantly inhibited MDA level and increased SOD and GSH-px levels in sevoflurane-induced newborn rat or human neuroglioma cells. Sun et al suggested that vitexin possesses cardioprotective action against DOX-induced cardiotoxicity through anti-oxidative effects (10). Bax is a Bcl-2 superfamily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with Vitexin significantly inhibited MDA level and increased SOD and GSH-px levels in sevoflurane-induced newborn rat or human neuroglioma cells. Sun et al suggested that vitexin possesses cardioprotective action against DOX-induced cardiotoxicity through anti-oxidative effects (10). Bax is a Bcl-2 superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Vitexin has anti-tumor, anti-oxidation, anti-virus, anti-inflammatory, anti-bacterial, antihypertensive and antispasmodic and other biological activities (10). In recent years, it has been reported that vitexin has anti-inflammatory effect (10). The present study was designed to investigate whether the protective effect of vitexin protects against sevoflurane-induced neuronal apoptosis and the mechanisms of this protective effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though synthetic antioxidants are widely used yet it is suspected to induce tumor formation in animals (Clayson et al, 1993;Hocman, 1988). Oxidative stress also generate inflammatory cascades, which are primarily mediated via inflammatory molecules including nitric oxide (NO), tumor necrosis factor-α (TNF-α), and interleukin (IL)-6 (Sun et al, 2016). During inflammation processes, NO, TNF-α, and IL-6 were produced from activated macrophages (Kitanaka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is tightly connected with inflammatory reactions (Sun et al, 2016). SK has anti-oxidative and antiinflammatory effects and is traditionally used to treat neuralgia, edema, pain, and inflammatory diseases in Korea.…”
Section: Introductionmentioning
confidence: 99%